2017
DOI: 10.1111/jeb.13026
|View full text |Cite
|
Sign up to set email alerts
|

Rapid differentiation and asynchronous coevolution of male and female genitalia in stink bugs

Abstract: Despite claims that genitalia are among the fastest evolving phenotypes, few studies have tested this trend in a quantitative and phylogenetic framework. In systems where male and female genitalia coevolve, there is a growing effort to explore qualitative patterns of evolution and their underlying mechanisms, but the temporal aspect remains overlooked. An intriguing question is how fast male and female genitalia may change in a coevolutionary scenario. Here, we apply a series of comparative phylogenetic analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
35
1
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(47 citation statements)
references
References 86 publications
7
35
1
4
Order By: Relevance
“…The degree of homoplasy can be considered as a rough proxy for the character rate evolution, implying that a higher rate (more changes) corresponds to a higher degree of homoplasy (lower CI values). In this respect, we conclude that the female genitalia characters in Saprininae tend to evolve more slowly than other characters, which corroborates a similar finding in stink bugs (Genevcius et al ., ). Interestingly, the mean value of RI (index of grouping) in female genitalia (Table ) is higher than those in somatic and male genitalia characters, thus suggesting that female genitalia bear important phylogenetic signal to define certain clades despite having lower CI than other categories.…”
Section: Discussionmentioning
confidence: 97%
“…The degree of homoplasy can be considered as a rough proxy for the character rate evolution, implying that a higher rate (more changes) corresponds to a higher degree of homoplasy (lower CI values). In this respect, we conclude that the female genitalia characters in Saprininae tend to evolve more slowly than other characters, which corroborates a similar finding in stink bugs (Genevcius et al ., ). Interestingly, the mean value of RI (index of grouping) in female genitalia (Table ) is higher than those in somatic and male genitalia characters, thus suggesting that female genitalia bear important phylogenetic signal to define certain clades despite having lower CI than other categories.…”
Section: Discussionmentioning
confidence: 97%
“…Even when male genital shape changes faster than female shape, female shape can be extremely variable (stink bugs; Genevcius et al. ). In cases where morphological variation in female genitalia are apparently subtle, careful quantification of shape variation has shown significantly different vaginal shapes despite some overlap in morphospace (watersnakes, Nerodia sipedon and N .…”
Section: Discussionmentioning
confidence: 99%
“…In these taxa, the lengths of the female common and separate spermathecal ducts are highly divergent among 17 species, and the length of the common spermathecal duct has coevolved with the genital process of males (Kotrba et al, 2014). Several other studies have found similar patterns of female genital diversity and coevolutionary variation between female and male genitalia (Breed, Leigh, & Speight, 2013;Genevcius, Caetano, & Schwertner, 2017;Hedrick, Natanson, Brennan, Antalek-Schrag, & Conith, 2019;Horton & Lewis, 2011;Ilango & Lane, 2000;Ishikawa, 1987;Yoshizawa, Ferreira, Kamimura, & Lienhard, 2014).…”
Section: Sloan and Simmonsmentioning
confidence: 91%